Authors Response: Reflections on Afro-descendant origin and the outcome of dengue fever cases in Colombia. (Colombia Medica, 2017)
1. lightly concludes that the Afro-Colombian population presented a lower risk of complications compared to the non-Afro-Colombian populationR / The course of the natural history of dengue disease, in Cases that make capillary leakage without adequate and timely management with hydration monitored and sustained for at least 48 hours, is towards the hypovolemic shock that is the main cause of other forms Serious and the route to death. The results in lethality do not reflect a higher volume of severe cases in the AfroColombian ethnic group compared to the Non AfroColombiana.